Spatial cognition and the avian hippocampus: Research in domestic chicks - Morandi-Raikova, Anastasia; Mayer, Uwe (Frontiers in Psychology, 2022)
In this review we discuss the functional equivalence of the avian and mammalian hippocampus, based mostly on our own research in domestic chicks, which provide an important developmental model (most research on spatial cognition in other birds relies on adult animals). In birds, like in mammals, the hippocampus plays a central role in processing spatial information. However, the structure of this homolog area shows remarkable differences between birds and mammals. To understand the evolutionary origin of the neural mechanisms for spatial navigation, it is important to test how far theories developed for the mammalian hippocampus can also be applied to the avian hippocampal formation. To address this issue, we present a brief overview of studies carried out in domestic chicks, investigating the direct involvement of chicks’ hippocampus homolog in spatial navigation.